Comparative efficacy of once-weekly semaglutide and SGLT-2 inhibitors in type 2 diabetic patients inadequately controlled with metformin monotherapy: a systematic literature review and network meta-analysis. (2nd September 2018) - Sharma, Rohini; Wilkinson, Lars; Vrazic, Hrvoje; Popoff, Evan; Lopes, Sandra; Kanters, Steve; Druyts, Eric
Abstract: Objective: Treatment intensification with additional anti-diabetic agents is recommended in type 2 diabetes (T2D) for patients inadequately controlled on metformin monotherapy. The present network meta-analysis (NMA) evaluated comparative efficacy and safety of once-weekly semaglutide and sodium-glucose co-transporter 2 inhibitors (SGLT-2is) in T2D patients inadequately controlled with metformin. Methods: Randomized controlled trials with ≥20 weeks duration were searched in EMBASE, MEDLINE, and CENTRAL. Primary efficacy outcomes were: change from baseline in HbA1c, weight, systolic blood pressure (SBP), post-prandial blood glucose (PPG), and fasting blood glucose (FPG). Treatment effects at 26 (±4) weeks were compared using Bayesian NMAs. Meta-regression and sensitivity analysis were used to address the trial heterogeneity. Results: Eight trials were found eligible for this NMA. Statistically significant reductions in HbA1c were observed with both 1.0 mg and 0.5 mg doses of once-weekly semaglutide when compared to SGLT-2is. The mean differences in change from baseline in HbA1c for once-weekly semaglutide 1.0 mg vs SGLT-2is ranged from −0.66% for canagliflozin 300 mg (95% Credible Intervals [CrI]: −0.82, −0.50%) to −1.11% for dapagliflozin 5 mg (95% CrI: −1.37, −0.85%). Once-weekly semaglutide 1.0 mg performed significantly better than all SGLT-2is of interest in reducing weight and improving FPG levels: however, SBP reduction was not statistically differentiable. Results of sensitivity analysis and meta-regressions aligned with base-case results. NMAs were not possible for PPG and safety outcomes, due to lack of data. Conclusion: Once-weekly semaglutide treatment is significantly better compared to SGLT-2is in achieving adequate glycemic control in T2D patients inadequately controlled with metformin monotherapy.